The Diagnostic Values of Pretreatment Serum Inflammation Markers and Lipoprotein in Men With Total Prostate-Specific Antigen Between 4 and 10 ng/ml - Li, Guangping; Shang, Zhenhua; Liu, Yihao; Yan, Hao; Ou, Tongwen (Frontiers in Medicine, 2020)
Background: The purpose of this study was to analyze the values of pretreatment serum inflammation markers, lipid, and lipoprotein for predicting the pathological results in men with total prostate-specific antigen between 4 and 10 ng/ml. Materials and method: A total of 611 eligible patients diagnosed with total prostate-specific antigen between 4 and 10 ng/ml and who received a transrectal ultrasound-guided prostate biopsy between January 2014 and December 2019 were included in our study. All the patients were divided into groups according to their pathological results and we collected the data of their pretreatment indicators of the blood routine and biochemistry. Results: The pathological results from prostate biopsies from 160 patients with prostate cancer and 451 patients with benign lesions. Age and total prostate-specific antigen values were significantly higher in patients with prostate cancer than those with benign lesions (P < 0.05). Red blood cell, platelet count, prealbumin, and triglyceride were significantly lower in patients with prostate cancer than those with benign lesions. Neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, lymphocyte- monocyte ratio, and apolipoprotein B were lower and apolipoprotein A-I was higher in the prostate cancer group than in the benign lesions group but not significantly (P > 0.05). Multivariate logistic regression revealed that age and total prostate-specific antigen could be independent predictors for pathological results (OR, 1.064, 95%CI, 1.031–1.098, P < 0.001; OR, 1.232, 95%CI, 1.061–1.429, P = 0.006). Conclusion: Higher age and total prostate-specific antigen were closely related to the pathological results. Prospective studies conducted with a large number of patients are needed to evaluate the diagnostic value of non-invasively pretreatment serum inflammation markers and lipoprotein for predicting the pathological results in men with total prostate-specific antigen between 4 and 10 ng/ml.